PENGARUH KOMUNIKASI INTERPERSONAL DOKTER GIGI MUDA TERHADAP KEPUASAN PASIEN DI RSGM IIK BHAKTI WIYATA KEDIRI - Multia Ranum Sari; Zakaria, Andika; Manampin Siahaan, Sahat; Ramadhani Kusumastiti, Anisa (Journal of Hospital Administration and Management (JHAM), 2025)
Interpersonal communication is an essential clinical competency in dental care that directlycontributes to patient experience and service quality. This study aims to analyze the interpersonalcommunication influence of dental clinical students based on the CLASS framework (Context–Listening–Acknowledgement–Strategy–Summary) and its relationship with patient satisfactionat RSGM IIK Bhakti Wiyata Kediri. This quantitative cross-sectional study involved 144 patientsselected using simple random sampling. Interpersonal communication was measured using the14-item CLASS instrument on a Likert scale. Reliability testing yielded a Cronbach’s Alpha valueof 0.84, indicating excellent reliability. Descriptive analysis showed that all CLASS components fellinto the very good category. Spearman correlation analysis produced a value of 0.000 (p-value <0.05), indicating that effective interpersonal communication between dental clinical interns andpatients leads to higher levels of patient satisfaction. Overall, interpersonal communicationamong dental clinical students was effective and consistent, and there was a significantrelationship between interpersonal communication and patient satisfaction